Public Perception of the Security of Public Service Facilities in the Era of the COVID-19 Pandemic - Azwaldi Azwaldi; Muliyadi Muliyadi; Rahmat Aswin Juliansyah (Eduvest - Journal of Universal Studies, 2022)
COVID-19 is a relatively new disease where the cause, origin of this virus is not known with certainty. This virus is very dangerous, very easily transmitted to fellow humans. This study aims to analyze Public Perceptions of the Security of Public Facilities Services in the Era of the Covid 19 Pandemic. This research is an analytical survey research with a cross-sectional study approach, which was carried out in 2020. The research respondents were people who were parents of students majoring in nursing, collecting The data was carried out using a google form questionnaire. The analysis was carried out through univariate and bivariate methods. From this research, it is known that respondents with the average age of respondents are 34.75 years, 85.7% of respondents are female, 90 respondents work as housewives, 99.1% are Muslim, and 125 respondents are rural people. While the bivariate results of this study stated that there was no correlation between age and public perception, there was no significant difference in the average community perception between men and women (p-Value 0.059), there was no difference in public perception regarding the safety of health care facilities. During the COVID-19 pandemic with the respondent's occupation, there was no difference in perception with religion (p-Value 0.362), and there was no significant difference in the average perception of the type of society (p-Value = 0.334).